Assessment of household insecticide-treated bed net ownership, utilization, and associated factors in Kersa Woreda, Jimma Zone, Southwest Ethiopia - Eshetu Mesfin Tadesse; Yirgalem Shibiru Baruda; Telila Mesfin Tadesse (Journal of Health, Population and Nutrition)
Abstract Background An estimated 40% of the world’s population lives in malaria-prone areas, there are 300–500 million malaria episodes worldwide, and at least one million malaria fatalities occur each year which makes malaria is a major public health concern [1]. In sub-Saharan Africa, malaria claims the lives of about 90% of all people worldwide. Today, there is a growing interest in using ITNs as one of the leading strategies for the prevention and control of malaria. Many studies on ITN use and associated factors have shown that factors influencing ITN use differ from place to place, with very few similarities; specifically, there are no studies conducted in the study area on ITN ownership, utilization, or associated factors. Methods A community-based cross-sectional study was conducted from April 2023 to June 2023. A multistage sampling technique was employed to recruit the study participants. From twenty Malaria kebeles, six kebeles were selected by the lottery method, and study households were selected by the systematic random sample technique. A total of 770 planned sample sizes were calculated by using a single population formula. A trained data collector was used to collect the data, and the data entry and analysis were performed with SPSS 27.0. Simple frequency distribution and descriptive analyses were performed to describe participants’ sociodemographic, ownership, and utilization. Bivariate and multivariate analyses were performed to determine associations between dependent and independent variables, with a p-value < 0.05 indicating statistical significance. Results Data were collected from a total of 766 study participants, for a response rate of 99.5%. The majority (89%) of the respondents had at least one ITN, and 83.5% of the households reported sleeping under the ITN the night preceding the survey. Knowledge about ITN as a preventive agent for malaria [AOR 2.028, 95% CI: 1.010, 4.070], the presence of pregnant mothers in the household [AOR 4.373, 95% CI: 1.70, 11.203], willingness to buy ITN [AOR 2.106, 95% CI: 1.330, 3.335] and home visited by health extension workers [AOR 2.002, 95% CI: 1.228, 4.540] were identified as factors associated with ITN utilization by households. Conclusion ITN ownership and utilization were 89% and 83.5%, respectively. Knowledge about the use of the ITN for preventing malaria, the presence of pregnant mothers in the household, willingness to buy the ITN, and home visits by HEW were identified as factors associated with ITN utilization. The ITN distribution for malaria cases and the mechanism for accessing the ITN in the market need to be considered by health authorities. Continuing to apply IEC/BCC interventions to increase the knowledge of the community on the ITN and of home visits and support the proper utilization of the ITN is highly important.